2011
DOI: 10.1104/pp.110.171322
|View full text |Cite
|
Sign up to set email alerts
|

Identical Amino Acid Substitutions in the Repression Domain of Auxin/Indole-3-Acetic Acid Proteins Have Contrasting Effects on Auxin Signaling    

Abstract: Auxin/indole-3-acetic acid (Aux/IAA) proteins function as repressors of auxin response gene expression when auxin concentrations in a cell are low. At elevated auxin concentrations, these repressors are destroyed via the ubiquitin-proteasome pathway, resulting in derepression/activation of auxin response genes. Most Aux/IAA repressors contain four conserved domains, with one of these being an active, portable repression domain (domain I) and a second being an auxin-dependent instability domain (domain II). Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 42 publications
(86 reference statements)
1
29
0
Order By: Relevance
“…Some Aux/IAA proteins lack an apparent domain II and have extended lifetimes compared with typical Aux/IAA proteins (Dreher et al, 2006), while others lack both domains I and II and might not function as repressors (Tiwari et al, 2004). Transgenic plants expressing stabilized Aux/IAA proteins with defective RDs display "high auxin" phenotypes, and it has been suggested that these phenotypes result from interactions of the stabilized defective repressors with activator ARFs, thus preventing association of wild-type Aux/IAA repressors and resulting in constitutive expression of auxin response genes (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some Aux/IAA proteins lack an apparent domain II and have extended lifetimes compared with typical Aux/IAA proteins (Dreher et al, 2006), while others lack both domains I and II and might not function as repressors (Tiwari et al, 2004). Transgenic plants expressing stabilized Aux/IAA proteins with defective RDs display "high auxin" phenotypes, and it has been suggested that these phenotypes result from interactions of the stabilized defective repressors with activator ARFs, thus preventing association of wild-type Aux/IAA repressors and resulting in constitutive expression of auxin response genes (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Aux/IAA proteins generally contain one (domain I) or two EARtype RDs in their N-terminal region, followed by a region containing a degron (domain II), and terminating in a PB1-type protein-protein interaction domain (domain III/IV) related to that in ARFs ( Figure 1A; Li et al, 2011;reviewed in Chapman and Estelle, 2009;Guilfoyle and Hagen, 2012;Salehin et al, 2015). Mutations in the conserved degron motif (GWPP) result in the stabilization of Aux/IAA proteins and generally result in plants having constitutive repression of auxin response genes and "low auxin" phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). 4 The "low auxin" phenotypes include seedlings with short hypocotyls and petioles, agravitropic roots, reduced numbers of lateral roots artIcLe addendum 35S:IAA19mImII-1 transgene (Fig. 2A); however, the DR5:GUS staining in roots was much reduced in 35S:IAA19mIB/ IAA7mII, III, IV seedlings compared to 35S:IAA19mImII-1 seedlings (Fig.…”
mentioning
confidence: 99%
“…When these stabilized proteins are constitutively expressed in transformed Arabidopsis plants, "high auxin" phenotypes are observed, and we have suggested a mechanism for how "high auxin" phenotypes arise in these plants. 4 In contrast, when an identical substitution is made in domain I of IAA17, plants expressing a stabilized version of this protein have "low auxin" phenotypes. We have suggested that these "low auxin" phenotypes are observed because IAA17 and proteins within the same clade have a second LxLxL repression domain, which continues to function when the LxLxL motif in domain I is rendered nonfunctional.…”
mentioning
confidence: 99%